The Influence of Hedonic Shopping Motivation and Shopping Lifestyle on Impulsive Buying in Official K-Pop Merchandise Purchases (A Study on the Monbebe Community in Indonesia) - Anggita Dini Fitria; Sonja Andarini (Universitas KH. Abdul Chalim Mojokerto, 2025)
Global technological advancements accelerated the spread of Korean culture, creating the Korean Wave. K-pop music is in high demand by the Millennial generation, and fans are very enthusiastic about their idol group merchandise. Buying excessive K-pop merchandise can lead to consumptive behavior, such as impulse buying, which encourages hedonistic behavior in individuals. The shopping lifestyle also plays a role in this phenomenon. This study examines how hedonic shopping motivation and lifestyle affect impulse purchases of official K-pop merchandise (a study of the Monbebe community). This research methodology is quantitative research with a survey method. Samples were taken from the Monbebe community using non-probability sampling techniques with 100 respondents. Google Forms was used to collect data, and the multiple linear regression method was used to analyze it. The research findings show that impulse buying behavior is significantly and partially influenced by hedonic shopping motivation and shopping lifestyle when buying official K-pop merchandise.